Deadly transfers and the global playground : transnational security threats in a disorderly world - Mandel, Robert, 1949- (Praeger, 1999)
This comprehensive study provides an integrated analysis of the global security environment and the consequent blossoming of ominous flows or "deadly tranfers". It includes the behaviour of rogue states, terrorist groups, transnational criminal organizations and deviant individuals.